RISK-BASED CAPITAL AND TAKAFUL INSURANCE PERFORMANCE: THE MODERATING ROLE OF FIRM SIZE - Lestari, Nimas Dewi; Meldona (Online Journal of Islamic Management and Finance (OJIMF), 2025)
This study examines the impact of Risk-based Capital (RBC) on Takaful’s financial performance, focusing on company size as a moderation factor. The RBC value is an insurance company’s benchmark in assessing the ability to meet insurance and reinsurance commitments. Overall, a good RBC level can reinforce a company’s value advantage. Based on resource-based theory, which discusses the value possessed by a company, it is explained that the size of a company can provide a positive prospectus signal for investors in terms of the health and performance of the company. The research methodology used in this study is Moderated Regression Analysis (MRA) with a quantitative approach. This research is focused on Islamic insurance companies in Indonesia that have received permits from the Financial Services Authority (OJK) from 2019 to 2023. The results of this study show that the amount of RBC allocation has a significant effect on the financial performance of Islamic insurance companies (takaful) in Indonesia. However, the size of the company does not moderate the influence of RBC on the financial performance of takaful companies in Indonesia. Insurance companies, both large and small, must be able to effectively allocate RBCs so that companies can meet claims obligations and maintain the stability of the company’s financial health. RBC can assist insurers in formulating more effective risk management strategies so that insurers can increase customer and stakeholder confidence and maximize their financial performance.